Renegade Siege - Cole, Judd (New York Leisure Books, 1996)
Born the son of a great chief and raised by frontier settlers, Touch the Sky returns to his father's people, and with the help of his white friends, hopes to protect his tribe from a murderous attack that could destroy the settlers and the tribal camp alike.
Keywords: Western stories -- Western radio programs